Efficacy of oral methylcobalamin in treatment of vitamin B12 deficiency anemia in children. Issue 12 (1st July 2017) - Verma, Deepti; Chandra, Jagdish; Kumar, Praveen; Shukla, Shailaja; Sengupta, Shantanu
Abstract: To demonstrate the efficacy of oral methylcobalamin in treating vitamin B12 (vitB12) deficiency anemia, our prospective observational study enrolled 28 children with both macrocytic anemia and low holotranscobalamin (HoloTC) levels. Their hematological and biochemical parameters pre‐ and posttreatment at 1 month were compared. Hemoglobin showed mean increase of 2.89 g/dl ( P  < 0.001), rising above 10 g/dl in 24 patients (85.7%). Reticulocytes peaked at 1 week. Mean fall in mean corpuscular volume of 24.83 fl ( P  < 0.001) and mean improvement in platelets of 122, 100/μl ( P  = 0.001) were noted, and mean rise in HoloTC and vitB12 were 111.36 pmol/l ( P  < 0.001) and 918.34 pg/ml ( P  < 0.001), respectively. Thus, initial responses to oral methylcobalamin in children with vitB12 deficiency anemia were adequate.